Cosmic Panel – An Alternative Source for Solar Panel - VSVG. Theekshana (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Solar Panel converts the sunlight into electrical energy. Efficiency of Solar panel depends on the weather conditions and temperatures. The minimum temperature required for working of a solar panel is 10 degrees Celsius-30 degree Celsius. Hence, we cannot use solar panels at very low temperatures. For example in space and at Polar regions. The alternative for this solar panel can be a cosmic panel. The idea of designing this panel is for the energy sources while travelling in space.